The Cult of Eagle in the Mythology of the Khangalassians - Arkady P. Isaev; Peter S. Fedotov; Prokopiy R. Nogovitsyn; Victor P. Nogovitsyn; Victor Y. Gabyshev (Пернатые хищники и их охрана)
The cult of eagle in the beliefs of the Yakutian (Sakha) people was described in detail in the beginning of the 20th century in the articles of V.M. Ionov (1913) and L.J. Shtenberg (1925). In recent years, the question of the semantics of the image of an eagle in the traditional culture of the Yakuts was addressed by U.P. Suzdalova (2020), the meanings of this bird of prey in mythological representations of the Sakha and Buryats by V.V. Ushnitsky (2021). Besides that, in a number of works related to the mythology of the Yakutian people, there is a mention of the eagle cult for Sakha (Kulakovsky, 1923; Alekseev, 1984; Gogolev, 2002, etc).